L.N. Tolstoy, M. Heidegger, and A. Gilyazov about the essential human 'self' - A.M. Sayapova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper deals with the problem of the resonant similarities in the texts by L.N. Tolstoy, M. Heidegger, and A. Gilyazov. The research is based on the data of the literary works of the authors mentioned above: “Anna Karenina” by L.N. Tolstoy; “Philosophy of the Country Road” and “Creative Landscape” by M. Heidegger; “Let's Pray” by A. Gilyazov. The aim of the research is to reveal the resonant similarities of the texts under study to conceptualize the fiction expression of the essential content of the human “self”, which is the most important factor of any literary work stimulating the interest of the translator in the translated piece. The tasks of the research are as follows: 1) to reveal the resonant similarities of the texts of three authors, which are seemingly different from each other; 2) to demonstrate that these seemingly distant similarities, when hermeneutically conceptualized, may serve as meaningful in our revelation of the universal ontological phenomena about the human being; 3) to demonstrate that the revelation of resonant similarities in ontological characteristics of the inner “self” of the person is the evidence that the essential “self” of the human being as a universal part of a personality serves as the basic criteria in the evaluation of a human being, their thoughts and actions. This essential source is meant to attract the translator, to be in the focus of their view as it is the natural content that unites the author and their translator. The methodological basis uniting the texts of three authors under consideration is seen as the ontological definition of a word provided by M. Heidegger. His statement that the essential source, even based on different languages, must be the same (“A Dialogue on Language between a Japanese and an Inquirer”) has been accepted in our paper as a terminus a quo, in our reflections on the word of fiction presented in three languages. The prospect of our research lies in the possibility to construct the fiction variability of the notion “essential” content of the human “self” depending on the author's approach.